FAULTING IN THE LITHOSPHERE AND ASSOCIATED PROCESSES: A REVIEW OF RESULTS OF THE ALL-RUSSIA TECTONOPHYSICS CONFERENCE HELD AT THE INSTITUTE OF THE EARTH’S CRUST, SIBERIAN BRANCH OF RAS - K. Zh. Seminsky; S. I. Sherman; A. V. Cheremnykh (Геодинамика и тектонофизика)
Results of the All-Russia conference “Faulting and associated processes in the lithosphere: tectonophysical analysis” are reviewed. It was held on 11–16 August 2014 at the Institute of the Earth’s Crust, Siberian Branch of RAS in Irkutsk, Russia. Several reports were presented by invited foreign researchers.